Comparative Analysis of Caffeine Content in Cold and Hot Brewed Robusta Coffee Using High-Performance Liquid Chromatography (HPLC) - Irma Rahmawati; Shofian Habib Asrori (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Coffee is one of the most popular beverages globally, cherished for its unique taste, aroma, and the stimulating effects of its caffeine content. The proliferation of creative coffee shops has introduced various new methods for enjoying coffee, including cold and hot brew techniques. These processing techniques can significantly influence the physicochemical characteristics of coffee, particularly its caffeine content. This study compares the caffeine content in Robusta coffee using cold and hot brewing techniques. The hot brew coffee was prepared using water at approximately 96°C with a French press for six minutes. In contrast, the cold brew method involved brewing with water at room temperature (20-25°C) using a French press, followed by storage for 12 hours in a refrigerator (2-8°C). Qualitative analysis involved examining the color reaction, while quantitative analysis was conducted using High-Performance Liquid Chromatography (HPLC). HPLC is a highly accurate method that is extensively used in the food and pharmaceutical industries. The results indicated that the caffeine content in cold-brewed Robusta coffee was significantly higher, with a concentration of 44.63 μg/mL ± 0.199% and a Relative Standard Deviation (RSD) of 0.4459%. Conversely, hot-brewed coffee showed a caffeine concentration of 23.96 μg/mL ± 0.278%, with an RSD of 1.1602%. The parametric Analysis of Variance (ANOVA) revealed a significance value of 0.000 (p < 0.05), indicating a significant difference in caffeine levels between hot-brewed and cold-brewed coffee. These findings suggest that the choice of Robusta coffee processing technique can be crucial for individuals with specific health conditions seeking to manage their caffeine intake.